ANGIOTENSIN-(1-7): A NOVEL SMALL MOLECULE FOR THE TARGETED TREATMENT OF TRIPLE NEGATIVE BREAST CANCER - Soto Pantoja, David R (Wake Forest University, 2009)
ABSTRACT Soto-Pantoja, David Ricardo ANGIOTENSIN-(1-7): A NOVEL SMALL MOLECULE FOR THE TARGETED TREATMENT OF TRIPLE NEGATIVE BREAST CANCER Dissertation under the direction of E. Ann Tallant, Ph.D., Professor and Patricia E. Gallagher Ph.D., Associate Professor Triple negative breast cancer (TNBC), an aggressive breast tumor that disproportionately affects young and minority women, is associated with a poor survival rate regardless of stage at diagnosis due to development of distant metastases. Tumors from women with TNBC lack estrogen receptors and progesterone receptors and have basal expression of the human epidermal growth factor receptor 2 (HER2), severely limiting therapeutic strategies. The purpose of this study was to determine whether angiotensin-(1-7) [Ang-(1-7)], an endogenous peptide hormone that activates the AT(1-7) receptor mas, inhibits the growth of triple negative breast cancer cells and tumors and identify the molecular mechanisms for the inhibition of cancer cell growth. Injection of MDA-MB-231 cells into the mammary fat pad of athymic mice resulted in triple negative breast tumors that were treated for 28 days with either saline or Ang-(1-7). The average tumor volume from mice treated with the heptapeptide was approximately 3-fold less than the size of tumors from control animals (170.8 ± 21.4 mm3 vs. 546.7 ± 87.9 mm3; n = 5, p < 0.05) and tumor weight was reduced from 1.0 ± 0.2 g in the saline-treated mice to 0.5 ± 0.1 g in Ang-(1-7)-treated mice (n = 5, p < 0.05). The reduced size of Ang-(1-7)-treated tumors was associated with low immunoreactivity to Ki67, a proliferation marker (84.2 ± 8.2 compared to 41 ± 7.6), suggesting that Ang-(1-7) attenuates cell growth. Activity of the MAP kinases ERK1 and ERK2 was reduced in tumors of Ang-(1-7)-treated mice which was associated with a receptor-mediated increase in the MAP kinase phosphatase DUSP1 (1.01 ± 0.1 relative gene expression in tumors from saline-treated mice compared to 1.78 ± 0.13 in tumors from Ang-(1-7)-treated mice). The decrease in tumor growth of Ang-(1-7)-treated mice was also associated with a reduction in the endothelial cell marker CD34 (a decrease in vessel density from 87.8 ± 6.4 in tumors from saline-treated mice to 32.0 ± 7.0 in tumors from Ang-(1-7)-treated mice, p < 0.05), suggesting that the heptapeptide inhibited angiogenesis. The reduced vessel density in Ang-(1-7)-treated tumors correlated with a 59% decrease in placental growth factor (PlGF) and a 72% reduction in vascular endothelial growth factor (VEGF), effects blocked by pre-treatment with siRNAs to the MAP kinase phosphatase DUSP1. These results are in agreement with studies showing that patients receiving subcutaneous administration of Ang-(1-7) showed a decrease in circulating PlGF. In another set of studies, Ang-(1-7) reduced the growth of lung tumor xenografts, The Ang-(1-7)-mediated reduction in lung tumor xenografts was mediated,in part, by a reduction in tumor angiogenesis and a decrease in VEGF protein and mRNA. Ang-(1-7) reduced tubule formation by human endothelial cells by more than 40% at a 10 nM dose, a response which was blocked by pre-treatment with the specific Ang-(1-7) receptor antagonist [D-Pro7]-Ang-(1-7). Moreover, the heptapeptide significantly reduced new blood vessel formation by more than 50% in the developing chick chorioallantoic membrane assay, an effect attenuated by the Ang-(1-7) receptor antagonist [D-Pro7]-Ang-(1-7). Taken together, these results suggest that Ang-(1-7) inhibits angiogenesis in vivo through activation of an AT(1-7) receptor. Based on the anti-proliferative and anti-angiogenic properties of the heptapeptide, Ang-(1-7) may be an effective, first-in-class compound for the treatment of triple negative breast tumors targeting the specific AT(1-7) receptor mas.
Keywords: Angiotensin; Angiogenesis; Breast Cancer; MAP Kinase; Phosphatase